Impact of E-Commerce Website on Small Tourism Enterprises in Quang Binh, Vietnam - Van, Chung Nguyen; Tu, Luc Tran (Journal of Asian Business Strategy, 2017)
The purpose of this research is evaluate the economic impact of using E-Commerce website to promote small and medium tourist enterprise (SMEs) in Quang Binh, Vietnam. Our research used two methods to collect data. First, we developed survey then interview 8 expert on ecommerce website and 100 technical economic student, the will be organized and analysis to determine how ecommerce impact on small tourism firm in Quang Binh. Secondly, an experimental website was created to evaluate the impact of occupancy rate on SMTEs. The results showed that website marketing is an effective marketing tool for backpacker and managers who have pursued a well thought out online advertising strategy as well as responded promptly to emails from clients. Furthermore, room occupancy had increased ranging from 12% to 34% due to their website. However there are some firms has room occupancy still not increased at all. This research also help owners made effort to promote their websites more effectively.